1995
DOI: 10.1152/ajpgi.1995.268.4.g553
|View full text |Cite
|
Sign up to set email alerts
|

Moluccella laevis lectin, a marker for cellular differentiation programs in mouse gut epithelium

Abstract: We have assembled a system for testing the hypothesis that changes in glycoconjugate production represent markers for defining developmental, spatial, and environmental influences on the proliferation and differentiation programs of various mouse gut epithelial cell lineages. Multilabel immunohistochemical methods were used to survey the interactions of purified lectins with 1) normal fetal, neonatal, and adult FVB/N mouse gut, 2) gastric and intestinal isografts harvested at various developmental stages, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Indeed there is a probability where misspecification of these cells might lead to a gain of expression in UEA1 lectin. Under normal conditions, this specific lectin is expressed exclusively by the mucous surface cell in the mouse gastric epithelium (9). Nevertheless, future development of specific markers for the different gastric precursor cells should allow the accurate evaluation of the exact role for BMP signaling on the specification of these cell subpopulations.…”
Section: Bmpr1amentioning
confidence: 99%
“…Indeed there is a probability where misspecification of these cells might lead to a gain of expression in UEA1 lectin. Under normal conditions, this specific lectin is expressed exclusively by the mucous surface cell in the mouse gastric epithelium (9). Nevertheless, future development of specific markers for the different gastric precursor cells should allow the accurate evaluation of the exact role for BMP signaling on the specification of these cell subpopulations.…”
Section: Bmpr1amentioning
confidence: 99%
“…An LSAB2/HRP staining kit (DAKO Japan) was used as the secondary antibody reaction system. Gastric pit cells were visualized using fluorescein-5-isothiocyanatelabeled CTB lectin (Sigma, St Louis, MO) binding as previously reported (6,7).…”
Section: Animalsmentioning
confidence: 99%
“…Anguilla anguilla agglutinin (15)(16)(17). Histochemical studies with these lectins suggested that there was an increase in pit cell number in the zymogenic gastric units of transgenic mice (e.g.…”
Section: The Effects Of Ablating Mature Parietal Cells On Other Gastrmentioning
confidence: 99%